An Evidence-Based Review of Dietary Supplements on Inflammatory Biomarkers in Obesity - Cruz Sánchez, Jacob Jonatan; Treviño de Alba, Carolina; De la Garza, Ana Laura (Enviro Research Publishers, 2018)
Obesity is a multifactorial chronic disease characterized by the hypertrophy and hyperplasia of the adipose tissue accompanied by low-grade chronic inflammation, which is in turn related to cardiometabolic diseases. The main treatment for obesity involves lifestyle changes, however, there are several factors that can prevent or impact successful weight loss in obese subjects. Recently, dietary supplements have been considered for their potential anti-inflammatory effect in obesity. Relevant literature sought in PubMed database focuses on human randomized placebo controlled trials to analyze the effect of dietary supplements on inflammatory biomarkers in obesity. However, there is a lack of existing evidence that the supplements are safe to use, and thus unfit for recommendation. Therefore, the objective of this evidence-based review is to analyze the current body of literature for evidence of the anti-inflammatory effects of dietary supplements, especially in regards to treating obesity.